Implementasi UU Nomor 22 Tahun 2001 tentang Kebijakan Penjualan BBM Eceran dalam Perspektif Fiqh Siyāsah - Ummu Khoiriah (Universitas Islam Negeri Raden Fatah Palembang, 2024)
The implementation of the Oil and Gas Law in the sale of retail Fuel Oil (BBM) in Lampah Village, Kedamean District, Gresik Regency, shows that many retail fuel sellers do not have business licenses. Fiqh Siyāsah's analysis of this policy is relevant to the act of hoarding fuel from petrol stations and selling at higher prices due to the long distance from petrol stations. Retail fuel sellers have not fully complied with the Oil and Gas Law. The purpose of this study is to determine the implementation of the Oil and Gas Law on the fuel sales policy and reviewed with Fiqh Siyāsah. The research uses empirical legal methods with qualitative descriptive techniques. Data was obtained through interviews, observations, and documentation, and analyzed based on the Oil and Gas Law and Islamic legal theories. The results of the study show that retail fuel sales in Lampah Village are effective, but the implementation of the Oil and Gas Law faces obstacles to supervision. The perspective of Fiqh Siyāsah can be a solution to improve the implementation of the retail fuel sales policy in Lampah Village. The suggestions given are policy socialization, cooperation between Village Heads and the Government, as well as counseling from BPH Migas and petrol stations.